2002
DOI: 10.1088/0960-1317/12/6/306
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the mechanical behavior of an electrically actuated microbeam

Abstract: We present a nonlinear model of electrically actuated microbeams accounting for the electrostatic forcing of the air gap capacitor, the restoring force of the microbeam and the axial load applied to the microbeam. The boundary-value problem describing the static deflection of the microbeam under the electrostatic force due to a dc polarization voltage is solved numerically. The eigenvalue problem describing the vibration of the microbeam around its statically deflected position is solved numerically for the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
231
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(240 citation statements)
references
References 13 publications
9
231
0
Order By: Relevance
“…We assume the microbeam to be placed under near-vacuum conditions (no damping), which represents a worst-case scenario. The pull-in voltage of this microbeam based on a static analysis [7,27] is 3.38 V, and accounting for the transient effect, it is 3.11 V. By calculating the natural frequency of this microbeam, we found that its fundamental natural period is close to 0.1 ms. Hence, the microbeam experiences the mechanical shock load of T=1.0 ms as quasi-static load and of T=0.1 ms as dynamic load.…”
Section: Response Of Mems Devices Employing Clamped-clamped Microbeamsmentioning
confidence: 93%
See 2 more Smart Citations
“…We assume the microbeam to be placed under near-vacuum conditions (no damping), which represents a worst-case scenario. The pull-in voltage of this microbeam based on a static analysis [7,27] is 3.38 V, and accounting for the transient effect, it is 3.11 V. By calculating the natural frequency of this microbeam, we found that its fundamental natural period is close to 0.1 ms. Hence, the microbeam experiences the mechanical shock load of T=1.0 ms as quasi-static load and of T=0.1 ms as dynamic load.…”
Section: Response Of Mems Devices Employing Clamped-clamped Microbeamsmentioning
confidence: 93%
“…We assume the microbeam to be placed under nearvacuum conditions (no damping), which represents a worst-case scenario. The pull-in voltage of this microbeam based on a static analysis [7,27] is 0.652 V, and accounting for the transient effect it is 0.6 V. Figure 11(a) shows the time response of the microbeam when actuated by a voltage load V dc = 0.36 V and subjected to a mechanical shock pulse of amplitude 400 g and duration 1.0 ms. Here, W max /d is the maximum deflection of the microbeam at x = L normalized to d, and t is the nondimensional time, as defined in (5).…”
Section: Response Of Mems Devices Employing Cantilever Microbeamsmentioning
confidence: 99%
See 1 more Smart Citation
“…For small vibration of micro-ring around the static deection, the linear natural frequency can be considered as the resonant frequency of the system with negligible error [37]. Using the proposed nite-element formulation and omitting the static deformation results, the linear natural frequency of the system under applied DC voltage can be studied.…”
Section: Modeling Of Circular Ringsmentioning
confidence: 99%
“…In the "large-displacement" regime, the tensile stresses must be taken into account; this results in nonlinear partial differential equations (PDEs), such as the Von Karman equation for plates, and, as a consequence, in nonlinear models. The most common way of handling these nonlinear PDEs consists in linearizing them close to a working point, as in [3][4]. This approach can lead to excellent results, provided the linearization hypothesis holds.…”
Section: Introductionmentioning
confidence: 99%